If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3x + -1) = 12x + -2 Reorder the terms: 4(-1 + 3x) = 12x + -2 (-1 * 4 + 3x * 4) = 12x + -2 (-4 + 12x) = 12x + -2 Reorder the terms: -4 + 12x = -2 + 12x Add '-12x' to each side of the equation. -4 + 12x + -12x = -2 + 12x + -12x Combine like terms: 12x + -12x = 0 -4 + 0 = -2 + 12x + -12x -4 = -2 + 12x + -12x Combine like terms: 12x + -12x = 0 -4 = -2 + 0 -4 = -2 Solving -4 = -2 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 2n+60=4n+6 | | 14x+6y=36 | | 56.75p+3.95=150.00 | | -20+15-22z=31 | | 2x+4(3x+8)=-80 | | y+2=-0.25(x+-4) | | 3y(y+8)=0 | | 280=14x | | 3(1-3d)=2(-4d-4) | | 56.75+3.95p=150.00 | | 4z+3=4z+3 | | x^4-8x^2-240=0 | | 9x+12=x-4 | | 8-2(-5+4)=10 | | y-2=-.25(x-4) | | -12+k=28 | | 5x+3=12x+15 | | 7-2x+6=4x-5 | | (4x-2)*(x+2)*0.5= | | 2n-3=5n+12 | | 25+1x=4+8x | | H(0)=x^2-6x+5 | | 5[x-2]=30 | | (4x-2)*(x+2)= | | s+2[s+3]+[4s-5]=148 | | 5x-22=77 | | 2y+2x^2=8x-8 | | y-0=.5(x-0) | | ax+5bx=7a-c+2ax | | 8x-10=85 | | -3=7-y | | 666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666+9d=2.88 |